Effect of yarn cross-sectional shape on resin flow through inter-yarn gaps in textile reinforcements. (January 2018) - Endruweit, A.; Zeng, X.; Matveev, M.; Long, A.C.
Abstract: Axial flow through gaps between aligned straight yarns with realistic cross-sectional shapes, described by power-ellipses, was analysed numerically. At a given fibre volume fraction, equivalent gap permeabilities have a maximum at minimum size of elongated tapering parts of the gap cross-section and a ratio of gap width to height near 1. When the yarn spacing is given in addition to the fibre volume fraction, calculated maximum and minimum values for the equivalent permeability of inter-yarn gaps, which occur at near-rectangular and lenticular cross-sections, differ by factors of up to 3.3. Novel approximations for the shape factor and the hydraulic diameter in Poiseuille flow were derived as a function of the fibre volume fraction, the yarn cross-sectional aspect ratio and the geometrical parameter describing the shape of the power-elliptical yarn cross-section. This allows the equivalent gap permeability to be predicted with good accuracy for any fibre volume fraction and yarn cross-section.